2023
DOI: 10.1002/jobm.202200624
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide and codon usage biases involved in the evolution of African swine fever virus: A comparative genomics analysis

Abstract: Since African swine fever virus (ASFV) replication is closely related to its host's machinery, codon usage of viral genome can be subject to selection pressures. A better understanding of codon usage can give new insights into viral evolution. We implemented information entropy and revealed that the nucleotide usage pattern of ASFV is significantly associated with viral isolation factors (region and time), especially the usages of thymine and cytosine. Despite the domination of adenine and thymine in the viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 139 publications
2
1
0
Order By: Relevance
“…AT bias was observed in all the six genes irrespective of clade, which is consistent with a previous report [52]. Noteworthy is the strong AT bias but weak selective pressure in EP153R, which is consistent with prior observations that natural selection derived from host-dependent selection is important for the removal of CG dinucleotides from viral genomes [53][54][55], while also suggesting differences, especially at the gene level.…”
Section: Discussionsupporting
confidence: 91%
“…AT bias was observed in all the six genes irrespective of clade, which is consistent with a previous report [52]. Noteworthy is the strong AT bias but weak selective pressure in EP153R, which is consistent with prior observations that natural selection derived from host-dependent selection is important for the removal of CG dinucleotides from viral genomes [53][54][55], while also suggesting differences, especially at the gene level.…”
Section: Discussionsupporting
confidence: 91%
“…The PR2 diagram illustrates an imbalance in the frequencies of A3, U3, G3 and C3 codons in ASFV, indicating that natural selection plays a significant role in moulding the virus’s codon preferences. Furthermore, analysis using ENC and neutral plots supports the notion that factors beyond mutation pressure contribute to ASFV’s codon usage patterns, aligning with previous research findings [ 53 ]. The neutrality plot analysis also indicated that natural selection and mutation pressure both participate in ASFV CUB.…”
Section: Discussionsupporting
confidence: 86%
“…The GC content (35.95%) characterizes ASFV as an AT-rich DNA virus. ASFV's preference for using AT nucleotides over GC nucleotides in all its coding sequences has been observed in a comparative genomics analysis of ASFV (Pu et al, 2023). Other viruses with a similar AT nucleotide composition include Hantaan viruses (Ata et al, 2021), Hepadnaviridae (Deb et al, 2020), Flaviviridae (Yao et al, 2019), lyssaviruses (Zhang et al, 2018), PEDV (Chen et al, 2014), PDCoV (He et al, 2019), and SARS-CoV-2 (Hou, 2020).…”
Section: Discussionmentioning
confidence: 94%